2014
DOI: 10.1200/jco.2013.52.8877
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Fertility Concerns and Preservation Strategies in Young Women With Breast Cancer

Abstract: A B S T R A C T PurposeMost research regarding fertility in young women with breast cancer has focused on long-term survivors. Little is known about how fertility concerns affect treatment decisions or fertility preservation strategies at the time of initial cancer diagnosis. Patients and MethodsAs part of an ongoing prospective multicenter cohort study, we surveyed women with newly diagnosed early-stage breast cancer at age Յ 40 years. The baseline survey included sociodemographic, medical, and treatment data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
265
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 336 publications
(296 citation statements)
references
References 26 publications
20
265
3
8
Order By: Relevance
“…Partridge et al 4 reported that fertility after treatment was a significant concern for approximately 60% of young women with early breast cancer and that fertility concerns would influence the treatment decisions of 26% of women 6 . As cure rates continue to improve, clinical advances to develop less gonadotoxic therapy and to intervene more effectively so that survivors can achieve their reproductive goals will be required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partridge et al 4 reported that fertility after treatment was a significant concern for approximately 60% of young women with early breast cancer and that fertility concerns would influence the treatment decisions of 26% of women 6 . As cure rates continue to improve, clinical advances to develop less gonadotoxic therapy and to intervene more effectively so that survivors can achieve their reproductive goals will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the longterm toxicities of breast cancer treatment are of increasing relevance, and several studies have found that fertilityrelated concerns greatly affect quality of life for young breast cancer survivors [3][4][5][6] . Such issues are likely to become more important given that the number of women delaying childbirth is increasing 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Many young patients with breast cancer have concerns on fertility when discussing with their oncologist about adjuvant therapy; these concerns may influence their treatment decisions [5][6][7]. Taking into account the effect of fertility issues on patients' quality of life, the American Society of Clinical Oncology recommends that oncologists discuss the risk of infertility and fertility preservation options in patients with cancer as early as possible before treatment starts [18].…”
Section: Discussionmentioning
confidence: 99%
“…dose dense chemotherapy). The estimate of effect is based only on one study (Ruddy et al 2014; online reference list).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation